Magnetohydrodynamic (MHD) Free Convective Flow past an Infinite Vertical Porous Plate with Joule Heating - Johana, Sigey K.; Okelo, Jeconia, A; Gatheri, Francis K; Ngesa, Joel O. (My University, 2013)
This work addresses the problem of Magnetohydrodynamic laminar unsteady flow of an incompressible electrically conducting fluid past an infinite vertical porous plate. It investigates how joule heating affects the velocity and tem-perature profiles of the fluid flow subjected to transverse magnetic field. The research examines specific equations of MHD flow which are solved numerically by finite difference approximations, using computer programme. The nu-merical results of this study reveal that an increase in joules heating parameter causes an increase in the velocity and temperature profiles uniformly near the plate but remain constantly distributed away from the plate, implying that the flow field of the MHD free convective flow is influenced substantially by the strength of Joules heating near the wall of the plate and at the mainstream
Keywords: Incompressible Flow; Electrically Conducting; Joule Heating